Play the art: Artistic value in video games - Jancsovics, Klaudia (Replay. The Polish Journal of Game Studies, 2022)
Playing a game does not mean that we are doing something childish and useless. Using a new technology to express our feelings and raise the awareness of social issues does not mean we cannot call it art. If we go back in time, we can realize that there has always been a resistance to novelty and machines. Sometimes, they were even considered harmful. The same life cycle happens with video games: they are valuable in many ways, they are far more developed than they were twenty years ago, and they have even reached a stage where we can find art in them. But how can they be art? Is the answer in the story or in the audiovisual elements?